2019
DOI: 10.3390/cells8070722
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lymphoblastic Leukaemia Cells Impair Dendritic Cell and Macrophage Differentiation: Role of BMP4

Abstract: Dendritic cells and macrophages are common components of the tumour immune microenvironment and can contribute to immune suppression in both solid and haematological cancers. The Bone Morphogenetic Protein (BMP) pathway has been reported to be involved in cancer, and more recently in leukaemia development and progression. In the present study, we analyse whether acute lymphoblastic leukaemia (ALL) cells can affect the differentiation of dendritic cells and macrophages and the involvement of BMP pathway in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…BMP-4 directly induces the osteogenic differentiation of BMSCs by activating the Smad signaling pathway [ 38 ]. Recently, many studies have reported that BMPs induce the polarization of M2 type macrophages [ 41 , 42 , 57 , 58 ]. Lee et al [ 57 ] reported that BMP-6 secreted by renal cancer cells can bind to BMPR-II on macrophages and then phosphorylate Smad5 in target cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP-4 directly induces the osteogenic differentiation of BMSCs by activating the Smad signaling pathway [ 38 ]. Recently, many studies have reported that BMPs induce the polarization of M2 type macrophages [ 41 , 42 , 57 , 58 ]. Lee et al [ 57 ] reported that BMP-6 secreted by renal cancer cells can bind to BMPR-II on macrophages and then phosphorylate Smad5 in target cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies have reported that the expression of BMP-4 is decreased in the serum of patients with DM and the calvarial defects of a DM rat model [ 39 , 40 ]. In addition, Martínez et al and Valencia et al reported that BMP-4 could induce macrophages to the M2 type by enhancing the secretion of IL-10 [ 41 , 42 ]. Therefore, BMP-4 may be a viable loading cytokine for 3D bioprinting to stimulate the healing of bone defects in patients with DM.…”
Section: Introductionmentioning
confidence: 99%
“…M2 macrophages stimulate mesenchymal stem cell proliferation and osteogenic differentiation through BMP-2 signaling (53). Conversely, in acute lymphoblastic leukemia BMP-4 is secreted to drive anti-inflammatory myeloid phenotypes, with dendritic cell immunosuppressive polarization, reduced M1 pro-inflammatory signature, and increased M2 macrophage generation (10). BMP-4 secreted from bladder cancer cell lines favored the polarization of monocytes and macrophages into the M2 macrophage phenotype (54).…”
Section: Discussionmentioning
confidence: 99%
“…BMPs regulate myeloid potential indirectly through stromal osteoblast lineages for increased homing of HSCs in bone marrow (8,9). Acute lymphoblastic leukemia cells produce BMP-4 to impair differentiation of macrophages and dendritic cells, and maintain a unique pro-tumorigenic microenvironment (10). BMP-2 ligand promotes immunomodulation of macrophages and their induction of bone marrow stroma ontogenesis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Though both capable of expressing M2-associated genes, splenic TAMs stimulated the proliferation of T-ALL cells more potently compared to BM-TAMs, demonstrating the highly plastic nature of TAMs under different microenvironments [24]. Valencia et al also reported that ALL cells released Bone Morphogenetic Protein 4 (BMP4) to induce immunosuppressive dendritic cells and generate M2-like macrophages, which produced low TNFα and high CCL2, IL-6 and IL-10 [25]. Lastly, a recent report found that stromal interaction molecule 1 (STIM1) and STIM2 mediated the pathologic cancer-induced inflammation in the TME of T-cell ALL.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%